Imprinting: When Early Life Memories Make Food Smell Bad - Rayes, Diego Hernán (2016)
A recent study has found that pathogen exposure early in the life of the nematode Caenorhabditis elegans leads to a long-lasting aversion that requires distinct sets of neurons for the formation and retrieval of the imprinted memory.